Is it worth it? The rates of return from informal venture capital investments - Mason, Colin M; Harrison, Richard T (Journal of Business Venturing, 2002)
Despite growing interest in venture capital, there is a paucity of information on the rate of return to these investments and the limited research that is available refers almost entirely to portfolio returns for venture capital funds. The investment returns to business angels have been virtually ignored. This paper provides the first attempt to analyse the returns to informal venture capital investment using data on 128 exited investments from a survey of 127 business angel investors in the UK. The paper finds that the distribution of returns is highly skewed, with 34% of exits at a total loss, 13% at a partial loss or break-even, but with 23% showing an IRR of 50% or above. Trade sales are the main way in which business angels harvest their investments. The median time to exit for successful investments was 4 years. Large investments, large deal sizes involving multiple coinvestors, and management buyouts (MBOs) were most likely to be high-performing investments.